Misi ANALISIS PROBLEMATIKA SOSIAL Pelaksanaan Amanat Agung sebagai Kontribusi bagi Misi dalam Konteks Indonesia: Prolematika Misi - Malik Bambangan; Stenly R. Paparang (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2026)
The Great Commission of the Lord Jesus speaks of the sending out of the disciples by Jesus to go and make disciples of all nations. There is an assumption that its implementation today applies only to disciples of Christ, not to the church, contains only evangelism, and is considered unnecessary. This study identifies the challenges faced in the implementation of the Great Commission, analyzes its contribution to interfaith dialogue and cooperation, and assesses the social impact of the implementation of the Great Commission in the context of Indonesian pluralism. This research uses a qualitative method with a descriptive approach, through the process of collecting data from various literatures and interpreting it to draw conclusions. The results show that there are several challenges and opportunities in the implementation of the Great Commission, including resistance, government regulation, social disparity, economic inequality, and social and religious tensions. Keywords: Social Problems, Great Commission, Christian Mission, Pluralism, Indonesia, Interfaith Dialogue, Evangelism